PENGARUH POLA ASUH ORANG TUA TERHADAP AKHLAK KARIMAH PESERTA DIDIK KELAS VIII DI SMP PLUS MUDA PRAKARYA - Safitri, Ananda Laila; Edy (Dakwatussifa: Journal of Da'wah and Communication, 2024)
This research was conducted to determine whether or not there is an influence between parental parenting patterns and the morals of class VIII students at SMP Plus Muda Prakarya . This research uses a quantitative descriptive method, a correlation model of 2 variables, which consists of the independent/independent variable, namely moral character and the dependent variable: parenting style. This research included all 27 class VIII students at SMP Plus Muda Prakarya. The technique used for sampling is a saturated sample. The data collection instruments in this research were documentation and questionnaires. The data analysis technique used is simple linear regression Conclusion Based on the data analysis explained in the previous chapter, it can be concluded that there is an influence between variable. Judging from the results of the simple regression analysis, the significance value obtained is smaller than 0.05, namely 0.000 < 0.05, so H0 is accepted and H1 is rejected, Parental Parenting Patterns (X) have an influence on Student Morals (Y). The level of influence between variable This means that the parenting style towards the morals of Class VIII SMP Plus Muda Prakarya is in the "Quite Strong" category.